Technological Change, Entry, and Stock-Market Dynamics: An Analysis of Transition in a Monopolistic Industry - Datta, Bipasa; Dixon, Huw (American Economic Review, 2002)
Technological Change, Entry, and Stock-Market Dynamics: An Analysis of Transition in a Monopolistic Industry by Bipasa Datta and Huw Dixon. Published in volume 92, issue 2, pages 231-235 of American Economic Review, May 2002